G227(P) A qualitative study to capture parental views on the transition of care process from paediatric to young adult diabetes services. (12th March 2018) - Pandya, AA; Halpin, L; Barnes, D; Libby, M; Endean, J; Rogers, L
Abstract : Aims: An increasing number of children are presenting with long-term conditions that require transition into adult services. This can be a stressful and daunting prospect for both the child and their parents. The aim of this pilot study was to collate the views of parents of children with Type 1 diabetes, whom would be transitioning in the near future. Eliciting their understanding and concerns relating to this process should help our transition team make appropriate changes, to ensure adequate support, preparation and explanations are given to current and future applicable families. Methods: An online anonymous survey (using Survey Monkey© software) was sent to 37 parents of children, aged 13 to 17 years, within our Paediatric Diabetes service. Results: We received 18 responses from a total of 37 parents. 56% of parents had not heard of transition of care services prior to this survey. 88% were unsure about what transition entailed, and in a free-text box expressed concerns about a lack of knowledge regarding this process. 72% of parents felt that transition of care had not been appropriately discussed – 100% wanted more information. 72% of responders would appreciate a group transition meeting with other families, whom are also soon to transition. Conclusions: Our Paediatric Diabetes service is not adequately discussing and involving patients and parents in transition of care from an early stage, which is causing parental concern. All responders requested more information about the process of transition. Further education should therefore be provided to applicable parents and patients, including the opportunity to attend group meetings, which will allow for additional peer-support. Limitations of this pilot included a low response rate (49%), with only the views of parents being obtained and considered. We therefore plan to replicate this qualitative survey in February 2018, after a collaborative parent and patient transition evening, with the aim to capture both parental and patient views. Furthermore, we plan to use our experiences and feedback to assist with the development of other transition services with our Trust and the local Diabetes Network.